2022
DOI: 10.1038/s41467-022-33186-z
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable production of hydrogen with high purity from methanol and water at low temperatures

Abstract: Carbon neutrality initiative has stimulated the development of the sustainable methodologies for hydrogen generation and safe storage. Aqueous-phase reforming methanol and H2O (APRM) has attracted the particular interests for their high gravimetric density and easy availability. Thus, to efficiently release hydrogen and significantly suppress CO generation at low temperatures without any additives is the sustainable pursuit of APRM. Herein, we demonstrate that the dual-active sites of Pt single-atoms and frust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…As a typical reducible oxide, CeO 2 as active catalyst or additive has been widely investigated for the catalytic reactions involving H 2 O. As shown in Figure a, the H 2 O molecule is stably adsorbed on the ideal CeO 2 (110) surface, in which O and H atoms of H 2 O bond with Ce and O atoms of CeO 2 , respectively. With this adsorption configuration, the energy barrier of H 2 O dissociation on ideal CeO 2 (110) is 0.58 eV, which is significantly lower than the barrier of 1.12 eV on Pt(111) . Benefiting from the relatively large space between the Lewis acid and Lewis base, the adsorption of H 2 O molecules on the FLP sites induces a significantly closer distance between H 2 O molecules and the surface of CeO 2 (Figure b).…”
Section: Embedded Adsorption Configuration Of Small Molecules On Flp ...mentioning
confidence: 94%
“…As a typical reducible oxide, CeO 2 as active catalyst or additive has been widely investigated for the catalytic reactions involving H 2 O. As shown in Figure a, the H 2 O molecule is stably adsorbed on the ideal CeO 2 (110) surface, in which O and H atoms of H 2 O bond with Ce and O atoms of CeO 2 , respectively. With this adsorption configuration, the energy barrier of H 2 O dissociation on ideal CeO 2 (110) is 0.58 eV, which is significantly lower than the barrier of 1.12 eV on Pt(111) . Benefiting from the relatively large space between the Lewis acid and Lewis base, the adsorption of H 2 O molecules on the FLP sites induces a significantly closer distance between H 2 O molecules and the surface of CeO 2 (Figure b).…”
Section: Embedded Adsorption Configuration Of Small Molecules On Flp ...mentioning
confidence: 94%
“…In addition, ab initio molecular dynamics (AIMD) simulations were performed to investigate the stability of the SA-FLP catalysts, which shows that SA-FLP-2 and SA-FLP-3 are relatively stable and can maintain FLP sites at high temperatures (Figure S2). Furthermore, several groups have recently synthesized Pt 1 @CeO 2 catalysts with different morphologies, 24,49 indicating that the synthesis of the SA-FLP dual-active site catalyst is possible in the experiments. Subsequently, the dissociative activation of methane was investigated on SA-FLP-2 and SA-FLP-3.…”
Section: Effect Of Oxygen Vacancy Concentration On Methane Activationmentioning
confidence: 99%
“…Similarly, CeO 2 (110) presents the highest possibility for FLPs construction ( Huang, 2016 ; Zhang et al, 2017 ). Many studies have proposed that FLPs constructed on defective ceria possess high activities for many small-molecule activation (such as, H 2 , NO, CO 2 ) ( Mo et al, 2015 ; Stephan and Erker, 2015 ; Huang et al, 2018 ; Li J. et al, 2021 ; Li et al, 2022 ; Zhang et al, 2022 ; Zou et al, 2022 ). Qu’s group have explored the adsorption and activation of CO 2 on CeO 2 (110) surface by DFT calculations and found that CO 2 can be easily activated on defective CeO 2 and further activated on FLPs because of the more negatively charged oxygen of CO 2 , when compared to CO 2 on an ideal CeO 2 (110) surface ( Figure 6A ) ( Zhang et al, 2019 ).…”
Section: Electronic Properties Of Ceo 2 -Based Nan...mentioning
confidence: 99%
“…Furthermore, they synthesized a porous nanorods of CeO 2 ( PN -CeO 2 ) with a high surface Ce 3+ fraction and obtained an improved selectivity of 94% for cyclic carbonates. Subsequently, Zhang et al have designed a single-atom Pt anchored PN -CeO 2 catalyst (Pt 1 / PN -CeO 2 ) with dual-active sites of Pt single-atoms and FLPs on PN -CeO 2 to ensure the effective activation of both CH 3 OH and H 2 O for high efficient H 2 generation at low temperatures ( Figure 6E ) ( Zhang et al, 2022 ).…”
Section: Electronic Properties Of Ceo 2 -Based Nan...mentioning
confidence: 99%
See 1 more Smart Citation